Multi-Objective and Financial Portfolio Optimization of Carrier-Sense Multiple Access Protocols with Cooperative Diversity - Robles, Ramiro Sámano (2015)
8th International Workshop on Multiple Access Communications (MACOM2015), Helsinki, Finland.